Contribution to ophthalmology and jurisprudence made by the Filatov-Gernet family: formative years (Ukrainian Journal of Ophthalmology, 2025)
The paper presents the careers of outstanding representatives of the Filatov family, V.P. Filatov and M.M. Gernet, prominent scientists in the field of ophthalmology and law. It was shown that their personality development was influenced by the family, their parents, P.F. Filatov and N.A. Gernet, and other numerous family representatives. While studying at Moscow University, the young scientists demonstrated their talent, intelligence, and commitment to science, which helped them continue their career.
Keywords: Filatov V.P.; Gernet M.M.; biographical method; career; ophthalmology; jurisprudence